Loss of AZGP1 as a Superior Predictor of Relapse in Margin‐Positive Localized Prostate Cancer. Issue 16 (30th July 2016) - Bruce, Hannah M.; Stricker, Phillip D.; Gupta, Ruta; Savdie, Richard R.; Haynes, Anne‐Maree; Mahon, Kate L.; Lin, Hui‐Ming; Kench, James G.; Horvath, Lisa G.
Abstract : BACKGROUND: Positive surgical margins (PSMs) in localized prostate cancer (PC) confer a two‐ to three‐fold increased risk of biochemical relapse (BR). Absent/weak AZGP1 expression and Gleason grade ≥4 at the margin are each independent predictors of BR in patients with PSMs. Our study aimed to determine whether the biomarkers AZGP1 expression and Gleason grade at the site of a PSM are significant independent markers of biochemical and clinical relapse (CR) when modeled together and whether one of these biomarkers may be superior in its capacity to predict outcome. METHODS: A cohort of 275 consecutive patients with margin‐positive localized PC following surgery were assessed for Gleason grade and AZGP1 expression at the PSM. BR‐free survival was the primary end‐point, while CR‐free survival and PC‐specific death were secondary endpoints. Kaplan–Meier Analysis and Cox Proportional Hazards Modeling were performed. RESULTS: Absent AZGP1 expression was significantly associated with increased risk of BR ( P = 0.001) and PC‐specific death ( P = 0.02). Gleason grade ≥4 at PSM was associated with BR ( P = 0.02), CR ( P = 0.003), and PC‐specific death ( P = 0.004). On multivariable analysis, absent AZGP1 expression remained an independent predictor of BR (HR 2.4, 95%CI 1.5–3.9, P < 0.001) when modeled with Gleason grade at margin (HR 1.3, 95%CI 0.9–1.9, P = 0.16), preoperative PSA ( P = 0.002), seminal vesicle involvement ( P = 0.002), extraprostatic extension ( P = 0.001), Gleason score ( P = 0.01), adjuvant treatment ( P = 0.75), linear length of the involved margin ( P = 0.001) and margin number ( P = 0.09). CONCLUSION: Absent AZGP1 expression is an independent predictor of BR in margin‐positive localized PC and is associated with increased PC‐specific mortality in a Phase II study. Absent AZGP1 expression was superior to Gleason grade at PSM in predicting relapse and should be incorporated into subsequent clinical trials of post‐operative radiotherapy in men with margin‐positive PC. Prostate 76:1491–1500, 2016 . © 2016 Wiley Periodicals, Inc.